2021
DOI: 10.1007/s40520-021-02016-5
|View full text |Cite
|
Sign up to set email alerts
|

Changes in physical activity levels and relationship to balance performance, gait speed, and self-rated health in older Swedish women: a longitudinal study

Abstract: Background and aim Physical activity levels in older people often decrease and may mean impaired physical functioning leading to an increased fall risk. The aim of this study was to investigate self-reported change in physical activity dose and deterioration in balance performance, gait speed, and self-rated health (SRH) in older women between two time points in a follow-up study. Methods A cohort of community-living women, aged 69–79 years (n = 351) were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…In the present study, the proportions of cautious and abnormal groups were 20.3% and 11.5%, respectively, which are lower than a Swedish study of 351 women aged 69–79 years (median, 72.4 years) showed that the median OLS time was 19 s (interquartile range, 1.5–30) and 22.5 s (interquartile range, 2–30) for right-leg and left-leg standing participants with high exercise, respectively [ 19 ]. Impaired balance contributes to a wide range of negative health outcomes [ 20 ].…”
Section: Discussionmentioning
confidence: 75%
“…In the present study, the proportions of cautious and abnormal groups were 20.3% and 11.5%, respectively, which are lower than a Swedish study of 351 women aged 69–79 years (median, 72.4 years) showed that the median OLS time was 19 s (interquartile range, 1.5–30) and 22.5 s (interquartile range, 2–30) for right-leg and left-leg standing participants with high exercise, respectively [ 19 ]. Impaired balance contributes to a wide range of negative health outcomes [ 20 ].…”
Section: Discussionmentioning
confidence: 75%
“…In addition, it will be important to establish whether enhanced physical status and improved fall strategies contribute to independence and long-term life satisfaction. Previous studies have shown that older adults with a high level of physical activity have more functional skills and fewer difficulties performing the activities of daily living and that they value their autonomy and health better [ 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…It was demonstrated that gait variability could be treated by physical activity, in different frailty-related scenarios [34][35][36]. The knowledge of reference values may be helpful to develop specific exercise programs for this type of patients.…”
Section: Discussionmentioning
confidence: 99%